An open-label study of the pharmacokinetics and pharmacodynamics of dabigatran etexilate 150 mg once daily in Caucasian patients with moderate renal impairment undergoing primary unilateral elective total knee or hip replacement surgery. Issue 144 (August 2016) - Eriksson, Bengt I.; Mikuska, Zsolt; Feuring, Martin; Amiral, Jean; Haertter, Sebastian; Stangier, Joachim; Nehmiz, Gerhard; Weitz, Jeffrey I.
Abstract: Background: In adults with moderate renal impairment (creatinine clearance [CrCl] 30–50 mL/min) undergoing total hip or knee replacement (THR/TKR), the recommended dose of dabigatran etexilate is 150 mg once daily (qd). We investigated the steady state pharmacokinetics, pharmacodynamics and safety in these patients. Methods: Single-arm, open-label phase 4 study (NCT01184989 ) in Caucasian patients receiving dabigatran etexilate 75 mg 1–4 h after surgery and 150 mg qd on days 2–10 (TKR) or days 2–35 (THR). Plasma total dabigatran concentrations (day 6 ± 1) were determined by high-performance liquid chromatography tandem mass spectrometry and indirectly using the commercially available diluted thrombin time (dTT) assay (Hemoclot® Thrombin Inhibitors). Results: Of 112 patients (mean CrCl 42.5 mL/min, age 79.1 years, 69.6% female), 100 completed the study. Geometric mean trough and peak dabigatran concentrations were 47.5 ng/mL (10th–90th percentile 19.7–120) and 166 ng/mL (49.1–364), respectively. There were four major bleeding events and no venous thromboembolic events. Dabigatran concentrations determined from dTT (and falling within the assay range of 50–500 ng/mL) underestimated actual values by 7.6% (90% confidence interval 5.3, 9.9), which is within the acceptance limits of ± 15%. Conclusions: These findings in Caucasians with moderate renal impairment undergoing THR or TKR support the use of the 150 mg qd dose of dabigatran etexilate. With adequate set-up, calibration and quality control the dTT assay might be appropriate for situations, such as serious bleeding or a need for urgent surgery, where determination of dabigatran levels would be helpful. Highlights: Caucasian hip or knee replacement patients with moderate renal impairment received dabigatran etexilate 150 mg once daily Four of 100 patients had major bleeds and none had venous thromboembolism Results support this dabigatran dose in this patient population Results suggest that, if needed, the diluted thrombin time can be used to quantify dabigatran concentrations